Human rights violations are associated with forcibly displaced population’s mental health—a systematic review and meta-analysis - Felix Sisenop; Pallavi Chatarajupalli; Paul A. Bain; Hanna Kaade; Jutta Lindert (Frontiers in Public Health)
BackgroundLittle is known about the mental health consequences of human rights violations in forcibly displaced populations. Objective: The objectives of this systematic review are to examine: (1) the prevalence of mental health conditions among forcibly displaced persons; (2) to investigate methodological factors contributing to mental health conditions; and (3) associations between mental health conditions and human rights violations.MethodsWe conducted a systematic review with meta-analyses on the prevalence of anxiety, depression, and posttraumatic stress disorder among forcibly displaced populations and factors contributing to it by searching in databases MEDLINE (Ovid), Embase, Web of Science Core Collection (Clarivate), PsycINFO (EBSCO), Sociological Abstracts (ProQuest), and PTSDPubs (ProQuest). Additionally, we assessed the Global Peace Index. Pooled associations were calculated using a random-effects meta-analysis model. Subgroup analyses were performed for the Global Peace Index, sampling methodology, also we assessed risk of bias.ResultsOf the 8,555 records screened, 55 with n = 31,573 participants met the inclusion criteria (n = 15,714 males, females, n = 15,859 females). Most studies were cross-sectional (n = 49). The pooled prevalence rates were 38.90% (95% CI: 29.63; 48.17) for anxiety, 38.16% (95% CI: 32.16; 44.15) for depression and 39.62% (95% CI: 32.87; 46.36) for posttraumatic stress disorder. Analyses by level of human rights violations show anxiety, and depression prevalence rates were higher in countries with very low Global Peace Index than countries with high, moderate and low Global Peace Index (39.84% vs. 16.09%; 41.07% vs. 26.67%). Analyses by risk of bias indicate that the prevalence rate of PTSD was higher in studies with a high risk of bias compared to those with a very high risk of bias (49.27% vs. 29.79%). For anxiety, the prevalence rate was greater with random sampling compared to convenience sampling (44.71% vs. 36.87%). Depression and PTSD prevalence rates were higher with convenience sampling than with random sampling (38.67% vs. 37.70%; 42.83% vs. 35.50%).ConclusionOur review suggests that systematic continuous human rights violations are associated with mental health conditions in forcibly displaced persons. To prevent mental health conditions, it is necessary to reduce exposure to human rights violations in the countries forcibly displaced persons come from.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42017076535, PROSPERO registration: CRD42017076535.